Efektivitas Latihan Pelvic Floor Muscle Training (PFMT) terhadap Inkontinensia Urin pada Pasien Prostatectomy - Ahmad Mufid Sultoni; Ninuk Dian Kurniawati; Retno Indarwati; Amin Rahmawati Purwaningrum; Herminia Maria Ximenes (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to determine the effectiveness of Pelvic Floor Muscle Training (PFMT) exercise on urinary incontinence in patients undergoing or after prostatectomy surgery. The method used is a systematic review of articles from the Pubmed, Proquest, ScienceDirect, SAGE and Scopus databases. The results showed that PFMT exercise or other combination therapies could strengthen the pelvic muscles and train the pelvic nerves in patients with urinary incontinence, improve quality of life, and reduce levels of depression and anxiety. In conclusion, PFMT exercise can be applied to treat patients by preventing or reducing the intensity of urinary incontinence in patients with prostatectomy. Keywords: Urinary Incontinence, Pelvic Floor Muscle Training, Prostatectomy